2020
DOI: 10.1177/0300891620915784
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use among Italian smokers: patterns, settings, and adverse events

Abstract: Objective: Information is scanty on the patterns and settings of electronic cigarette use and on its possible adverse events. To fill the knowledge gap on these issues, we conducted a survey among ever-smokers attending smoking cessation services (SCS) in Italy. Methods: In 2016–2018, we enrolled 395 ever-smokers aged ⩾18 years who were current or former electronic cigarette users in 12 SCS from northern, central, and southern Italy. Results: In all, 12.4% of ever smokers were regular, 9.4% occasional, and 78.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
4
8
0
1
Order By: Relevance
“…Whereas the safety consequences of these products are still largely unknown [1], more and more concerns have been raised by independent research on public health consequences [1, [19][20][21]. In particular: (i) electronic cigarette use has been found to increase-rather than decrease-tobacco smoking in the general adult population [19] and has been associated with tobacco smoking initiation among adolescents [1, [22][23][24][25]; (ii) also never smokers or ex-smokers having quit since several years are attracted to these new products [21]; (iii) novel product users are more frequently dual users consuming the novel product where smoking is forbidden [26]; (iv) the role of electronic cigarette on smoking cessation is unclear and uncertain [1] and, as HTPs are tobacco products, the conversion from conventional cigarettes to HTPs should not be considered cessation [1]; and (v) electronic cigarettes increase the risk of renormalization of smoking in society [1, [27][28][29]. Moreover, a survey conducted in 12 European countries recently showed how a large proportion of ex-smokers using HTPs did not quit smoking switching to HTPs but they firstly quit and then relapsed to the use of tobacco [30].…”
Section: Of 10mentioning
confidence: 99%
“…Whereas the safety consequences of these products are still largely unknown [1], more and more concerns have been raised by independent research on public health consequences [1, [19][20][21]. In particular: (i) electronic cigarette use has been found to increase-rather than decrease-tobacco smoking in the general adult population [19] and has been associated with tobacco smoking initiation among adolescents [1, [22][23][24][25]; (ii) also never smokers or ex-smokers having quit since several years are attracted to these new products [21]; (iii) novel product users are more frequently dual users consuming the novel product where smoking is forbidden [26]; (iv) the role of electronic cigarette on smoking cessation is unclear and uncertain [1] and, as HTPs are tobacco products, the conversion from conventional cigarettes to HTPs should not be considered cessation [1]; and (v) electronic cigarettes increase the risk of renormalization of smoking in society [1, [27][28][29]. Moreover, a survey conducted in 12 European countries recently showed how a large proportion of ex-smokers using HTPs did not quit smoking switching to HTPs but they firstly quit and then relapsed to the use of tobacco [30].…”
Section: Of 10mentioning
confidence: 99%
“…A recent study conducted in Italy showed that almost all e-cigarette users among Italian smokers consumed liquids containing nicotine and most of them used these devices in indoor environments where conventional cigarette smoking is usually banned [48]. Consequently, to avoid the dual use (i.e.…”
Section: Alternative Tobacco Productsmentioning
confidence: 99%
“…A total of 14 studies were included 8,9,[19][20][21][25][26][27][28][29][30][31][32][33] , with a total sample size of 6827 cases. We summarized the prevalence of xerostomia for all smokers.…”
Section: The Prevalence Of Xerostomiamentioning
confidence: 99%